The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
1998
DOI: 10.1136/adc.79.6.488
|View full text |Cite
|
Sign up to set email alerts
|

Vitamin D receptor alleles predict growth and bone density in girls   Commentary

Abstract: Twin and family studies suggest that up to 75% of the variance in bone mineral density (BMD) is determined genetically and several candidate genes have been identified that might be involved in this process.1 Polymorphisms of the vitamin D receptor (VDR) gene causing diVerences in bone density between the homozygous haplotypes, were first described by Morrison et al in twin studies in an older female population.2 Subsequently, over 50 studies have been reported, examining the relation between BMD and VDR genot… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
24
2
4

Year Published

2001
2001
2012
2012

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 49 publications
(31 citation statements)
references
References 37 publications
1
24
2
4
Order By: Relevance
“…In contrast to the findings of previous studies reporting that VDR genotype was related to height among children and adolescents (46,47), we found no association between VDR genotype and height. In our study, there was a lower mean BMI associated with the VDR BsmI B allele and an increased mean WHR among women with the VDR FokI ff genotype but only for Hispanics.…”
Section: Discussioncontrasting
confidence: 57%
See 1 more Smart Citation
“…In contrast to the findings of previous studies reporting that VDR genotype was related to height among children and adolescents (46,47), we found no association between VDR genotype and height. In our study, there was a lower mean BMI associated with the VDR BsmI B allele and an increased mean WHR among women with the VDR FokI ff genotype but only for Hispanics.…”
Section: Discussioncontrasting
confidence: 57%
“…A polymorphism detected by the FokI restriction enzyme alters a translation initiation site (45). The VDR polymorphisms have been reported to influence growth and height in European and Australian Caucasian children (46,47). Several studies have reported that the untranslated region and/or the FokI polymorphisms are associated with cancer risk (48)(49)(50)(51)(52)(53)(54).…”
Section: Introductionmentioning
confidence: 99%
“…The impact of genetic determinants of bone tissue was evaluated in children and adolescents, because the optimal genetic effect is evident in children aged up to 20 years [21,22]. In studies conducted by Baroncelli et al, evaluating the association of VDR variability with bone mass in children in pre-pubertal period, no interactions have been reported between BsmI polymorphism and bone turnover markers (including osteocalcin), or bone mineral density [20].…”
Section: Discussionmentioning
confidence: 99%
“…Accordingly, a model taking into account the early influence of VDR-3 polymorphisms, calcium intake and puberty on BMD gain has been proposed to explain the relation between these genotypes and peak bone mass (Ferrari et al 1998a). Interestingly also, several investigators have noted a significantly lower height among women and men with the VDR-3 BB compared with Bb or bb genotypes (Barger-Lux et al 1995, Ferrari et al 1998c, Tao et al 1998, Lorentzon et al 2000. Considering the relationship between body size and bone size, as well as the influence of calcium intake on both body height and bone area during growth (Bonjour et al 1997), it is tempting to speculate that VDR-3 alleles together with environmental calcium might have an indirect and complex influence on peak bone mass through the regulation of skeletal growth.…”
Section: Vdr Gene Polymorphismsmentioning
confidence: 97%